DEVELOPMENT OF GAMES OF MORAL STORIES (GMS) BOOK BASED ON BOROBUDUR RELIEF FOR BUDDHIST SUNDAY SCHOOL STUDENTS AT ELEMENTARY SCHOOL - Suryaningratri, Asamurti; Ayuvadhana, Nandiya; Puja Setia Wati, Citta Ariya; Suranto, Suranto (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2022)
This study aims to develop Games of Moral Stories (GMS) book based on Borobudur relief and knowing book effectiveness for a student at Buddhist Sunday School (BSS) for the elementary school level. The research method used is the type of research and development (R&D) with the ADDIE development model. Data collection techniques used are questionnaires, documentation, observation, and interview methods. The data analysis technique used is descriptive qualitative. The result of this research is the creation of a book Games of Moral Stories based on Borobudur Relief for Buddhist Sunday School students at Elementary School. Games of Moral Stories book got a feasibility percentage of 80% from material expert dan 86% from media experts. Based on the results of expert validation, the Games of Moral Stories book is appropriate to be used as a medium for BBS learning elementary school level